Nitrate Leaching in an Argiudoll Cultivated with Sugarcane - Portocarrero, Rocio; Acreche, Martin Moises (2018)
The aim of the study was to quantify nitrate leaching from an Aquic Argiudoll cultivated with sugarcane in Tucumán, Argentina. Two field trials were conducted during the 2010/2011 and 2011/2012 seasons with the variety LCP 85-384. Treatments consisted of nitrogen fertilisation with urea with doses of 0 and 81 or 88 kg N/ha for second or third ratoon, respectively. Fertilisation was performed following standard cane farming recommendations in Tucumán on 26 October 2010 and 16 November 2011. In order to determine nitrate concentration, samples were taken from soil solutions at 85 cm depth using ceramic soil water suction samplers, while water flow was simulated with the LEACH-W model. There were similar trends in both seasons. In 2010/2011, unfertilised plots had no nitrates in soil solution, while fertilised plots leached nitrates from 29 to 57 days after fertiliser application, coinciding with the onset of percolating rains. In 2011/2012, although unfertilised plots had nitrates in solution, they were significantly less than in fertilised plots. In the latter, leaching time lasted from 16 to 34 days after nitrogen fertilisation. The main conclusions of this study are: (1) there is low nitrate leaching from sugarcane cultivation, in an Argiudoll, with frequent nitrogen fertilisation doses used in the production systems in Tucumán, and (2) nitrate leaching was observed at the onset of the rainy season, when both deep drainage of water and available nitrates are simultaneously present.